2022
DOI: 10.1002/hep4.1946
|View full text |Cite
|
Sign up to set email alerts
|

Body fat composition determines outcomes before and after liver transplantation in patients with cirrhosis

Abstract: Cachexia occurs in late stages of liver cirrhosis, and a low-fat mass is potentially associated with poor outcome. This study compared different computed tomography (CT)-derived fat parameters with respect to its prognostic impact on the development of complications and death before and after liver transplantation. Between 2001 and 2014, 612 patients with liver cirrhosis without hepatocellular carcinoma listed for liver transplantation met the inclusion criteria, including abdominal CT scan (±200 days to listi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Cachexia is the ongoing loss of body composition (skeletal muscle or fat mass), leading to progressive functional impairment. Muscle wasting is a well‐known phenomenon associated with decompensated cirrhosis, 32 and body fat distribution is also a marker of outcome in patients with liver cirrhosis after LT. An observational study found that lower visceral fat mass (HR: 1.403, 95% CI, 1.057–1.862, P = 0.019) significantly reduced the 1‐year OS after LT in patients with liver cirrhosis 33 . Unintentional weight loss is one of five domains of the Fried frailty phenotype 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Cachexia is the ongoing loss of body composition (skeletal muscle or fat mass), leading to progressive functional impairment. Muscle wasting is a well‐known phenomenon associated with decompensated cirrhosis, 32 and body fat distribution is also a marker of outcome in patients with liver cirrhosis after LT. An observational study found that lower visceral fat mass (HR: 1.403, 95% CI, 1.057–1.862, P = 0.019) significantly reduced the 1‐year OS after LT in patients with liver cirrhosis 33 . Unintentional weight loss is one of five domains of the Fried frailty phenotype 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation to BMI is based on the fact that an accumulation of inter‐ and intramyocellular fat is significantly dependent on the overall amount of body fat and can only be considered pathological in the context of BMI. A visceral fat area (VFA) exceeding 100 cm 2 indicated visceral obesity, 19 while the SFI was dichotomized at the upper tertile of the cohort (71.89 cm 2 /m 2 ) 23 . Sarcopenic obesity was defined as sarcopenia plus a simultaneous BMI ≥25 kg/m 2 9 …”
Section: Methodsmentioning
confidence: 99%
“…In other catabolic diseases, the data on body composition (in particular, adipose tissue), malnutrition and survival are still scanty. However, in selected populations, such as those with liver cirrhosis in wait list for transplantation, often affected by poor nutritional status, low SAT was associated with increased inflammation, decompensated cirrhosis and with increased risk of complications and death on transplant wait list, whereas increased visceral fat was a predictor of 1-year mortality after transplantation [45]. Also, Zhu et al [46] found that modifications of SAT negatively affected clinical outcomes in cirrhosis.…”
Section: Clinical Impact Of Adipose Tissue Wasting In Cachexiamentioning
confidence: 99%